Attitudes of Sports Development and Sports Management undergraduate students towards entrepreneurship: A university perspective towards best practice. Issue 8 (4th November 2014) - Jones, Paul; Jones, Amanda
Abstract : Purpose: – Given the high unemployment rates being experienced by graduates, the importance of small business start-up has increased significantly, with greater priority being placed upon the development of entrepreneurial skills across the educational sector. However, there is a limited literature considering the student experience and issues involved with supporting non-Business discipline students attaining entrepreneurial competencies. The purpose of this paper is to explore the attitudes and experience of Sports Development and Sports Management students towards entrepreneurship education, highlighting best practice from a pedagogical perspective. Design/methodology/approach: – Over 120 Sports Development and Sports Management students on an undergraduate degree were interviewed over a two year period using a semi-structured research instrument. The focus and content of the questionnaire was developed from prior studies undertaken in the field, measuring the impact and value of entrepreneurship education upon attitudes, knowledge and career choice. Findings: – The results found that Sports Development and Sports Management students were typically enterprising by nature due to their prior experience in coaching and training within their respective sports disciplines. The majority of students indicated that they were attracted to a future entrepreneurial career in a sports-related discipline. This was driven by the potential of an entrepreneurial career option and the limited alternative choices. Sports Development and Sports Management students were characterised by their mature attitudes towards their career development and future inclination regarding an entrepreneurial career choice. Practical implications: – The results will inform the teaching of entrepreneurship education to non-Business discipline specialist students in terms of the effective construction of entrepreneurship curriculum. Best practice in terms of customised subject informed teaching material, guest talks and interactive pedagogical practice are highlighted. Originality/value: – This study will be of interest to entrepreneurship education providers delivering content to non-Business disciplines at all levels and aid them in the construction of their curriculum to provide fit for purpose provision.